POLITICAL ASSESSMENT OF PROPOSED TOBACCO PRODUCT TAX INCREASE STATE OF MICHIGAN Organization Authors: NSA, NATL SMOKERS ALLIANCE (Tufts Archival Research Center, 2007)
Confidential; National Smoker’s Alliance Assessment of the proposed cigarette tax increase for 1994 in the state of Michigan. Reports on the National Smoker's Alliance response to the legislation and their strategies to defeat the ballot. Mentions that key strategy is "confusion," showing loopholes in the legislation.